ISO-Annoyance Lines for Selected Linked Pairs of Indoor Climate Parameters. - Santos, Arturo Martin B.
Most of the indoor climate research has been done in countries in the temperature region. Many of these are developed countries having resources to build good buildings and for indoor climate research. It has been a consensus in the developed societies that it is economically justified to aim at providing optimal indoor environments for students, office workers and others who work indoors. Either legislators, designers and builders in developing countries in tropical regions are often forced to use the expensive and possibly inappropriate standards from developed countries or they may adapt solutions which have no formal scientific basis. There is therefore a need for fundamental and applied research focused on the indoor climate needs of developing countries in hot and humid tropical regions. Achieving optimized partial improvements of the indoor climate may often be better than to know all optimal levels. The purpose of this study was to investigate the relative importance of temperature, noise, draft and window area when two of these parameters are linked. Thirty (30) heat-acclimatized subjects participated in 10 exposures in single person climate chambers. Each exposure lasted three hours. During an exposure, the subject was free to optimize the operative temperature at a link to either draft, noise or window area. For each pair of parameters, three linear links were tested. A reference exposure was furthermore included without any link. Results show that a decrease in operative temperature of 1 degree celcius gives the same decrease in annoyance as approximately 0.1 m/s decreased air velocity, 7 dB (A) decreased noise level or 0.5 m2 increased window area. The used trade off method may have numerous other research applications.